Exalting energy scavenging for triboelectric nanogenerator using silicon carbide particles doped polyvinylidene difluoride nanocomposite. (March 2023) - Shafeek, Shimna; Balakrishnan, Neethu T.M.; Fatma, Bushara; Garg, Ashish; J, Jabeen Fatima M.; Morton, Danny; Luo, Jikui; Raghavan, Prasanth
Abstract: Polymer materials, particularly piezoelectric polymers, have been extensively studied and implemented in triboelectric nanogenerators (TENG) owing to their ferroelectric properties, low cost and easy synthesis etc . This research is a comprehensive analysis on a novel nanocomposite of polyvinylidene fluoride (PVDF)/silicon carbide (SiC) nanoparticles as a triboelectric material, and fabrication of TENGs using the SiC-PVDF nanocomposite and polyamide (PA6) membrane combination. The composite film obtained from the phase inversion method with varying concentration of SiC nanoparticles is studied and compared with the pristine film prepared by solution casting. The results show that the inclusion of SiC nanoparticles could greatly enhance the β-phase content of the PVDF films, and significantly increase surface roughness and porosity of the SiC-PVDF nanocomposites. The TENG made with a PVDF film with 6 wt% of SiC shows an open circuit voltage of 850 V and a short circuit current of 20 µA under a frequency of 3.5 Hz, 1100 V and 42 µA under a frequency of 15 Hz at a load of 5 N. The TENG has a high-power output of 12.25 mW at 3.5 Hz, which is four times higher than that of the TENG using the film prepared using the solution casting method. This work provides an effective strategy for enhancing the output power of PVDF/PA6 TENGs through the addition of SiC nanoparticles with great application prospects for low power electronics and as active sensors. Graphical Abstract: ga1 Highlights: The crystalline phase in the PVDF is modified by doping with nanosized silicon carbide for TENG. The enhancement in triboelectric performance is evaluated by addition of SiC NPs in PVDF matrix. The SiC-PVDF phase inversion membrane exhibits superior performance as compared to solvent casted membranes. The optimal TENG will be a promising pair for application in power source for low-power electronics.